Editor's Note Vol. 11 (December 2023) - Alam, Firoz (MIST International Journal of Science and Technology, 2023)
Abstract not available <p style="background: white; box-sizing: border-box; line-height: 1.785rem; margin: 1.43rem 0px; color: rgba(0, 0, 0, 0.87); font-variant-ligatures: normal; font-variant-caps: normal; orphans: 2; text-align: start; widows: 2; -webkit-text-stroke-width: 0px; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; word-spacing: 0px;">MIJST, Vol. 11, December 2023 : xiii DOI: https://doi.org/10.47981/j.mijst.11(02)2023.454(xiii)